2009
DOI: 10.1021/ic900814b
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Spin Transition Temperature in FeII One-Dimensional Coordination Polymers: an Anion Based Database

Abstract: One-dimensional (1D) coordination polymers of formula [Fe(NH(2)trz)(3)]A.nH(2)O, {A = TiF(6)(2-), n = 0.5 (1) and n = 1 (2); A = ZrF(6)(2-), n = 0.5 (3) and n = 0 (4); A = SnF(6)(2-), n = 0.5 (5) and n = 1 (6); A = TaF(7)(2-), n = 3 (7) and n = 2.5 (8); A = GeF(6)(2-), n = 1 (9) and n = 0.5 (10), NH(2)trz = 4-amino-1,2,4-triazole} have been synthesized, fully characterized, and their spin crossover behavior carefully studied by SQUID magnetometry, Mossbauer spectroscopy, and differential scanning calorimetry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
72
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 80 publications
11
72
1
Order By: Relevance
“…To our knowledge, this is the first system with systematic control of the Fe-Fe interaction in the 1D triazole-coordinated iron(II) SCO complexes. Moreover, there is a noticeable difference between this and other studies that investigated the dependence of SCO behavior by spherical counter anions, as described in numerous previous reports and our compounds [24,25,[37][38][39][41][42][43]45,[52][53][54][55][56]. The relationship between ∆T 1/2 and the alkyl chain length is shown in Figure 18b.…”
Section: Fastener Effect Of Counter Ions On Sco For the [Fe(ii)(r-trzcontrasting
confidence: 58%
See 1 more Smart Citation
“…To our knowledge, this is the first system with systematic control of the Fe-Fe interaction in the 1D triazole-coordinated iron(II) SCO complexes. Moreover, there is a noticeable difference between this and other studies that investigated the dependence of SCO behavior by spherical counter anions, as described in numerous previous reports and our compounds [24,25,[37][38][39][41][42][43]45,[52][53][54][55][56]. The relationship between ∆T 1/2 and the alkyl chain length is shown in Figure 18b.…”
Section: Fastener Effect Of Counter Ions On Sco For the [Fe(ii)(r-trzcontrasting
confidence: 58%
“…Moreover, Garcia et al reported on the correlation between T 1/2 and the volume of the counter anion in the series of fluorinated inorganic divalent anions (TiF 6 2− , ZrF 6 2− , SnF 6 2− , GeF 6 2− , and TaF 7 2− ) salts of [Fe(II)(NH 2 -trz) 3 ] complexes, in addition to the related monovalent complexes [43].…”
Section: The Effect Of Counter Ion Size On Sco For the [Fe(ii)(r-trz)mentioning
confidence: 99%
“…In 2, the carboxylic group is kept away from the coordination sphere unlike in 3 thus demonstrating role of synthetic method in directing network construction through self-assembly. This is a crucial point for the design of 1D coordination polymer involving switchable Fe II spin crossover (SCO) centers with a MN 6 core [15][16][17][18]. A similar situation is also noticed in 1.…”
Section: Logistics For Network Constructionsmentioning
confidence: 72%
“…The family of thermochromic 1D iron(II) 1,2,4-triazole spin crossover (SCO) coordination polymers have attracted our attention in recent years due to their promising prospects in the thriving field of molecular electronics [15][16][17][18]. Such triazole based precursors not only provide appropriate ligand field strength but also favors the formation of CPs due to its dominant N1,N2 bridging mode ending up in high dimensional networks which are recognized for their ability to efficiently propagate elastic cooperative effects associated to the SCO event [116].…”
Section: Thermochromic Spin Crossover Materialsmentioning
confidence: 99%
See 1 more Smart Citation